2020
DOI: 10.1007/s13238-020-00768-w
|View full text |Cite|
|
Sign up to set email alerts
|

Novel and potent inhibitors targeting DHODH are broad-spectrum antivirals against RNA viruses including newly-emerged coronavirus SARS-CoV-2

Abstract: Emerging and re-emerging RNA viruses occasionally cause epidemics and pandemics worldwide, such as the on-going outbreak of the novel coronavirus SARS-CoV-2. Herein, we identified two potent inhibitors of human DHODH, S312 and S416, with favorable drug-likeness and pharmacokinetic profiles, which all showed broad-spectrum antiviral effects against various RNA viruses, including influenza A virus, Zika virus, Ebola virus, and particularly against SARS-CoV-2. Notably, S416 is reported to be the most potent inhib… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
174
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(185 citation statements)
references
References 60 publications
10
174
0
1
Order By: Relevance
“…28 Still, efforts to develop broadly acting antivirals via targeting DHODH continue and a recent study reported the discovery of two promising DHODH inhibitors S312 and S416 ( Figure 1) with low in vivo toxicity starting from a virtual screening. 34 Both compounds were able to inhibit the replication of different influenza A viruses, Zika-and Ebola virus, as well as, importantly, SARS-CoV-2. 34 Blocking de novo purine nucleotide biosynthesis…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…28 Still, efforts to develop broadly acting antivirals via targeting DHODH continue and a recent study reported the discovery of two promising DHODH inhibitors S312 and S416 ( Figure 1) with low in vivo toxicity starting from a virtual screening. 34 Both compounds were able to inhibit the replication of different influenza A viruses, Zika-and Ebola virus, as well as, importantly, SARS-CoV-2. 34 Blocking de novo purine nucleotide biosynthesis…”
mentioning
confidence: 99%
“…34 Both compounds were able to inhibit the replication of different influenza A viruses, Zika-and Ebola virus, as well as, importantly, SARS-CoV-2. 34 Blocking de novo purine nucleotide biosynthesis…”
mentioning
confidence: 99%
“…The inhibition or knockdown of such host proteins will block the viral replication, providing potential antiviral targets for drug development. Recently, novel and potent inhibitors of human dihydroorotate dehydrogenase (DHODH) were reported as broad-spectrum antiviral agents against RNA viruses including SARS-CoV-2 [94] . DHODH is a rate-limiting enzyme in the de novo pyrimidine nucleotide biosynthetic pathway that catalyzes the stereospecific oxidation of (S)‐dihydroorotate to orotic acid and finally generates uridine and cytosine, providing nucleotide resources for host cells as well as the viruses.…”
Section: Inhibiting the Viral Genome Replicationmentioning
confidence: 99%
“…The in vivo study revealed that S312 had excellent antiviral efficacy in influenza A virus-infected mice. S312/S416 and the approved drugs targeting DHODH (leflunomide/teriflunomide) thus have therapeutic potentials in combating SARS-CoV-2 [ 94 , 95 ].…”
Section: Inhibiting the Viral Genome Replicationmentioning
confidence: 99%
“…Maraviroc, an antagonist of chemokine receptor type 5 for HIV treatment, presents a typical HTA drug. In a remarkable study published in this journal, Xiong et al reported novel and potent inhibitors of human dihydroorotate dehydrogenase (DHODH) as broad-spectrum antiviral agents against RNA viruses including SARS-CoV-2 (Xiong et al, 2020).…”
mentioning
confidence: 99%